Spatial assessment of heavy metal contamination in agricultural soils of the lower Chancay–Huaral valley, Peru - Samaniego Vivanco, Tomás Daniel (2026)
Soil contamination by heavy metals (HMs) poses a potential threat to agricultural productivity and food security, particularly in rapidly developing coastal regions. This study evaluates the spatial distribution and contamination levels of cadmium (Cd), copper (Cu), lead (Pb), zinc (Zn), and manganese (Mn) in agricultural soils from the Huaral, Chancay, and Aucallama districts of the Lima region, Peru, an area undergoing urban expansion, mining concessions, and the establishment of a new international port. A total of 88 soil samples were analyzed for metal concentrations using microwave plasma atomic emission spectrophotometry (MP-AES), along with key physicochemical properties. Geostatistical interpolation techniques, including ordinary kriging (OK) and cokriging (CK), were applied to generate spatial prediction maps for each element. The geo-accumulation index (Igeo) and contamination factor (CF) were used to determine the contamination status. Mean Igeo values ranged from −0.59 to −0.46, while mean CF values ranged from 1.09 to 1.21, indicating generally unpolluted to moderately polluted conditions. Although maximum values reached 1.41 for Igeo and 4.21 for CF, these were spatially localized. Results revealed that most metal concentrations remained below the Peruvian Environmental Quality Standards for agricultural soils, suggesting predominantly natural geochemical origins. However, a small proportion of samples showed slight and localized exceedances (4.54% for Cd and 3.41% for Mn). For elements not regulated under national standards, international guidelines were considered, further supporting the absence of widespread anthropogenic contamination. Higher concentrations of Cd, Cu, Zn, Pb, and Mn were spatially clustered in the north-central sector of the study area, suggesting responses to soil properties such as pH, texture, and moisture. Notably, areas of higher concentration did not coincide with zones of higher contamination indices, indicating limited anthropogenic influence. However, proximity to urban expansion, mining activities, and port infrastructure highlights the need for continuous soil monitoring to prevent accumulation and ensure agricultural sustainability.